Classical right, new right, and voting behavior: Evidence from a quasi-natural experiment - Jesús Fernández-Villaverde; Carloz Sanz (American Enterprise Institute (AEI), 2024)
Due to a last-minute fight among the candidates, Vox, a party at the right end of the Spanish political spectrum, could not run in Santa Cruz de Tenerife, a relatively representative electoral constituency, in the general election of July 23, 2023. Since this fight was a power struggle within Vox unrelated to any fundamental in the constituency or ideological differences among the candidates, we can exploit this event as a quasinatural experiment to measure the effects of new parties on electoral outcomes. Using three different but complementary research designs (matching, synthetic controls, and a triple-difference analysis), we get to the same main result: Vox's presence significantly increases votes for the right as a whole. The increase in votes for the right caused by Vox's presence is particularly strong in areas with high unemployment. The presence of Vox also reduces protest votes but, on the other hand, votes for the left are unaffected.
Keywords: D72; N30; N40; Z13; 330; New parties; quasi-natural experiments; electoral outcomes